Nara Milanich Children of Fate. Childhood, Class, and the State in Chile, 1850-1930 - Candina, Azun (Cuadernos de Historia, 2010)
Duke University Press, Dirham and London, 2009, 356 páginas. ISBN 978-0-8223-4557-2